The Intestinal Absorption of Dietary Cholesterol by Hypercholesterolemic (Type II) and Normocholesterolemic Humans - Connor, William E. (1974)
The incomplete absorption of dietary cholesterol may represent an adaptive intestinal barrier that prevents hypercholesterolemia. To explore this mechanism, we compared cholesterol absorption in 15 normocholesterolemic and 6 hypercholesterolemic (type II) subjects fed background cholesterol-free formula diets with 40% of calories as fat. Each test meal consisted of a breakfast into which was incorporated scrambled egg yolk containing 300-500 mg of cholesterol and [4-(14)C]cholesterol (3-22 μCi), either naturally incorporated into the yolk cholesterol by previous isotope injection into the laying hen or added in peanut oil to the yolk of the test breakfast. In some instances [1α-(3)H]cholesterol was the radioactive marker. The radioactivity of the fecal neutral sterol fraction was determined in daily stool samples for the next 7 days to provide an estimate of unabsorbed dietary cholesterol. The amount of absorbed and reexcreted labeled cholesterol proved negligible. Most unabsorbed dietary cholesterol appeared in the stool on the second or third day after the meal, and 95% or more was recovered in the stool by 6 days. Plasma specific activity curves were usually maximal at 48 h. Normal subjects absorbed 44.5±9.3 (SD) of the administered cholesterol (range 25.9-60.3). Hypercholesterolemics absorbed the same percentage of cholesterol as normals: 47.6±12.6% (range 29.3-67.3). Absorption was similar whether the radiolabeled cholesterol was added to egg yolk or naturally incorporated in it (42.1±9.3 vs. 48.9±9.8%). Six normal subjects were fed a cholesterol-free formula for 4 wk, and then different amounts of cholesterol (110-610 mg/day) were added for another 4 wk. At the end of each period, single test meals containing either 110, 310, or 610 mg of cholesterol and [1α-(3)H]cholesterol were administered. Cholesterol absorption was 42.3±6.0% and 45.4±8.3% for the two dietary periods, respectively. The absolute cholesterol absorption was linearly related to the amount of cholesterol in the test meal, and absorption was not affected by background diets high or low in cholesterol content.